Mixed-species flocking is associated with low arthropod detectability and increased foraging efficiency by Yungas forest birds in Argentina - Mangini, Giselle; Mokross, Karl [UNESP]; Gandoy, Facundo; Areta, Juan Ignacio (Oxford Univ Press Inc, 2022)
Lay Summary center dot The theoretical framework used to understand mixed-species flocks formation posits that birds benefit by increasing their foraging efficiency. center dot It follows that birds are more likely to join mixed-species flocks when arthropod abundance decreases. However, we asked, what is the effect of the difficulty in detecting arthropods? center dot We put two ideas into a competition, whether the arthropod abundance or instead their detectability triggers the formation of mixed-species flocks. center dot We have found that the formation of mixed-species flocks is more prone to occur when arthropods are more challenging to find and not necessarily when they are scarcer. center dot We add a new perspective on the drivers of mixed-species flocking, showing that mixed-species flocks' participants achieve higher foraging success and that the capacity to find and recognize prey items may have a more significant effect triggering sociality than prey abundance. Mixed-species flocks presumably provide birds with antipredator and foraging benefits. The foraging benefits hypothesis predicts that a reduction in arthropod abundance will trigger flocking activity; however, flocking activity may also be influenced by the difficulty of detecting arthropods, a seldom explored possibility. We found that environmental traits (temperature and foliage density) combined with arthropod abundance explained arthropod detection by birds in the Yungas foothill forest of NW Argentina. Prey detection was inversely related to ambient temperature and foliage density while positively associated with arthropod abundance. Based on this result, we built a structural equation model using a latent proxy variable for arthropod detectability, arthropod crypsis, integrating ambient temperature, foliage density, and proportion of immature arthropods. This model allowed us to compare the relative importance of arthropod abundance and the difficulty in detecting prey items as predictors of flocking propensity. After 2 yr of studying 129 mixed-species flocks, 1,351 bird foraging sequences, and 25,591 arthropod captures, we found that the flocking propensity of birds was only significantly correlated with arthropod detectability and not with arthropod abundance. Flocking propensity peaked when the arthropod community was comprised of proportionately more immature and non-flying arthropods, the temperature was low, and the foliage cover was denser; all factors are contributing to a low arthropod detectability. Finally, we evaluated whether joining mixed-species flocks provided foraging benefits such as increased foraging efficiency. Individuals benefited from joining flocks by an average increase of their prey-capture attempt rate of 40%, while the search rate increased by 16%. Our results add a new perspective on the drivers of mixed-species flocking by showing that the capacity to find prey items may have a more significant effect than prey abundance per se.
Keywords: Aves andinas; abundancia de alimento; detectabilidad de presas; tendencia a formar bandadas mixtas; beneficios de forrajeo; Andean birds; flocking propensity; food abundance; foraging benefits; prey detectability